PELATIHAN METODE IDENTIFIKASI MOTORIK SISWA MENGGUNAKAN TES TGMD-2 DI DESA JAYALAKSANA - Trio Wibowo Sulaeman; Ekowati Ekowati; Aridhotul Haqiyah (An-Nizam, 2023)
The TGMD-2 test is one of the motion development tests developed by Ulirch in 1985. Ulrich D. A. from the School of kinesiology at the University of Michigan, has compiled a test to evaluate 250 basic motor skills (Test Of Gross Motor Development). TGMD-2 tests 12 basic movement skills which are divided into two subtests, namely locomotor and object control. This test is designed to assess the level of basic motor skills in children aged 3-10 years. This test is suitable for elementary school age students 7-10 years. In community service this time using the training method in the form of demonstrations related to the rules, movements and procedures for carrying out the TGMD-2 Test. The main target for this program is sports teachers who work at the Jayalaksana Village Elementary School, Kec. CabangBungin, Bekasi Regency.The purpose of implementing this program is to improve motor understanding of sports teachers through training in methods of identifying motor skills of elementary school students through the TGMD-2 test. The results obtained showed that the teacher representatives from each elementary school in Jayalaksana Village were able to provide good understanding and direction of the TGMD-2 test movements to 6 (six) students who were appointed as demonstrators in the demonstration of the TGMD-2 test movement. So it can be concluded that this Community service activity has an impact, namely being able to increase knowledge and information related to the material and implementation of the TGMD-2 Test for teachers who teach sports, as well as provide knowledge about the importance of motor development for elementary school students in Jayalaksana Village because they have It is the duty and responsibility of a teacher to know the progress of his students. Keyword:Motor Skills, TGMD-2 Test, Sports Teachers